1989
DOI: 10.1039/p19890002329
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of phenanthrene-9,10-quinone with benzoyl- and acetylmethylenetriphenylphosphoranes. Trapping of the o-quinone methanide intermediates

Abstract: The reaction of phenanthrene-9,lO-quinone ( I ) with the phosphorus ylide (2a) to give compounds (6a), (9a), ( I I ) , and (13) has been reinvestigated. Reaction of ( I ) with the phosphorus ylide (2b) afforded compounds (5b), (6b), and (9b). The transformations (5b) + (6b) and (6b) (5b) have also been studied. When the reactions between (1) and the ylides (2a,b) were carried out in the presence of ethyl vinyl ether both the expected products (17a,b) and (18a,b) and the unexpected products (20a,b) were obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

1990
1990
2003
2003

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…In 1989, Nicolaides et al reported that the reaction of benzoylmethylene(triphenyl) phosphorane ( 232, R = Ph) with phenanthrenequinone ( 215 ) in dichloromethane solution forms a mixture of the corresponding products 235 (R = Ph), 236 (R = Ph), 237 , and 238 , while using acetylmethylene(triphenyl)phosphorane ( 232 , R = Me) with the same quinone 215 leads to the formation of compounds 235 (R = Me) and 236 (R = Me).
…”
Section: Reactions With Wittig Reagentsmentioning
confidence: 99%
“…In 1989, Nicolaides et al reported that the reaction of benzoylmethylene(triphenyl) phosphorane ( 232, R = Ph) with phenanthrenequinone ( 215 ) in dichloromethane solution forms a mixture of the corresponding products 235 (R = Ph), 236 (R = Ph), 237 , and 238 , while using acetylmethylene(triphenyl)phosphorane ( 232 , R = Me) with the same quinone 215 leads to the formation of compounds 235 (R = Me) and 236 (R = Me).
…”
Section: Reactions With Wittig Reagentsmentioning
confidence: 99%
“…Reaction of Compound 3f with Ethoxycarbonyimethylene-(tripheny1)phosphorane 2c.-A solution of compound 3f (0.3 12 g, 1 mmol) and the ylide 2c (0.348 g, 1 mmol) in dry dichloromethane ( 5 cm3) was stirred at room temperature for 24 h. After removal of the solvent the residue was chromatographed on silica gel with hexane4ichloromethane (1 : 1 up to 0: m) and 8.49-8.75 (3 H, m); m/z 352 (M', 83%), 324 (loo), 309 (12), 281 (9), 253 (10) and 252 (23).…”
Section: Cis-3-(4-methoxyphenyl)-2-(4-methyiphenyi)-23-dihydro-phenan...mentioning
confidence: 99%
“…(93), ενώ με 2-μεθοξυ-φουράνιο δίνει τον εστέρα(96).COAr i^V^3 108Σε μια πολύ πρόσφατη εργασία περιγράφονται εκ νέου αντιδράσεις του(86) με τα αντιδραστήρια(91) και(87) προς τα προϊόντα(88) και(89), αλ λά με παράλληλο σχηματισμό και 1,4-βενζοξαζίνης, στη δεύτερη περίπτωση.Περιγράφεται επίσης η αντίδραση του (86) με ROH προς το προϊόν (110)134 .116Κατά την επίδραση των ημισταθερών υλιδϊων (117) έδωσε αρχικά ο-κινονιμινο μεθϊδια (Ζ-και Ε-) που κατά τη θέρμανση τους κυκλοποιήθηκαν προς τα συμπυκνωμένα πυριδινικά παράγωγα138 (118).Η μονοξίμη(111) κατά τη θέρμανση της σε διαλύματα μεθυλουποκατεστημένων αρωματικών ενώσεων (CH3-Ar), ισοκυκλικών (π.χ. τολουόλιο,139 .…”
unclassified